'The Elevation of Sensitivity over Truth': Political Correctness and Related Phrases in the Time Magazine Corpus. (18th July 2017) - Granath, Solveig; Ullén, Magnus
Abstract: This article is a quantitative and qualitative diachronic study of how the expression politically correct (PC) and related phrases are used in the American magazine Time from 1923 through 2006. The data show a dramatic increase in the frequency with which PC-phrases are used in the early 1990s. From this time onwards, the phrases are often used as a means of passing evaluative subjective opinions off as objectively reported facts, especially in reviews of cultural events, where they figure prominently. In contrast to earlier studies, our data show that PC-phrases are not inherently negative; this applies primarily to discourse on environment and business, where to be PC often implies being environmentally or socially conscious in a positive sense. Nevertheless, negative or ironic uses of the terms predominate. Most often they express criticism of unspoken cultural norms rather than being attempts to close down debate or criticizing the replacement of offensive terms by more neutral expressions.